Influence of the Work Environment and Communication on Employee Productivity at PT. Agro Lestari - Purwanto, Wahyu; Subandrio, Subandrio; Rudi Alhempi, Raden (Proceedings of the International Conference on Multidisciplinary Science (INTISARI), 2024)
This study investigates the impact of the work environment (WE), workplace communication (WC), and management policies (MP) on employee productivity (EP), with employee motivation (EM) acting as a moderating variable. The research was conducted at PT. Agro Lestari, utilizing a quantitative approach and total sampling of 30 employees. Data were collected through structured questionnaires and analyzed using Smart PLS (Partial Least Squares) to assess both direct and indirect relationships between the variables. The results show that WE, WC, and MP have significant direct effects on EP, while EM enhances these effects through mediation. The work environment and effective communication were found to significantly increase employee motivation, which in turn improves productivity. Additionally, fair and transparent management policies play a crucial role in motivating employees, further driving their performance. The findings highlight the importance of fostering a supportive work environment, clear communication channels, and sound management policies to enhance employee productivity, particularly in sectors like agriculture.